An Analytical Study of the Value of Tradition Merit of Heet Sibsong: An Analytical Study of the Value of Tradition Merit of Heet Sibsong - Upasanto (Chomchaypol), Phra Taweesap; Phrakrupariyatsatorn (RATANABUTH JOURNAL, 2024)
The objective of this thesis were: 1) To study the tradition merit of Heet Sibsong. 2) To study the value the tradition merit of Heet Sibsong. 3) To analytical the value of the tradition merit of Heet Sibsong. This is documentary research. The research results found that the tradition merit of the Heet Sibsong is a merit-making ceremony that is performed every month of the year and has been passed down continuously by combining the culture, traditions, and beliefs of Buddhism, Brahmanism, and beliefs in ghosts, spirits, spirits, guardian angels, and sacred things. It has an influence on the way of life of the Isan people from birth to death. The importance of the tradition merit of the Heet Sibsong is to learn about the purpose of the merit-making ceremony, various practices for a good and happy and prosperous way of life and to conserve it. The value of social relationships and the way of life of the villagers who live together with mutual assistance and support. It creates social relationships and practices that affect the family, along with cultivating and nurturing the mind so that children grow up to be good people with morality. The relationship between the home and the temple which is the center, the spirit, the venue for the event, and the relationship between ethics and aesthetics, thoughts, and practices. The components of the religious ceremony play an important role in helping to promote, namely, creating a mental feeling for stability and safety that can continue living, creating value in terms of aesthetics and ethics in the role of a mental feeling that is stable and safe, being a tool of society, preserving, enjoying beauty and the role of local arts and culture.